Long-term within- and between-subject biological variation of 29 routine laboratory measurands in athletes - Diaz-Garzon, Jorge; Fernandez-Calle, Pilar; Aarsand, Aasne K.; Sandberg, Sverre; Coskun, Abdurrahaman; Carobene, Anna; Jonker, Niels; Itkonen, Outi; Bartlett, William A.; Buno, Antonio (Clinical chemistry and laboratory medicine, 2022)
Within- and between-subject biological variation (BV) estimates have many applications in laboratory medicine. However, robust high-quality BV estimates are lacking for many populations, such as athletes. This study aimed to deliver BV estimates of 29 routine laboratory measurands derived from a Biological Variation Data Critical Appraisal Checklist compliant design in a population of high-endurance athletes. Eleven samples per subject were drawn from 30 triathletes monthly, during a whole sport season. Serum samples were measured in duplicate for proteins, liver enzymes, lipids and kidney-related measurands on an Advia2400 (Siemens Healthineers). After outlier and homogeneity analysis, within-subject (CV ) and between-subject (CV ) biological variation estimates were delivered (CV-ANOVA and log-ANOVA, respectively) and a linear mixed model was applied to analyze the effect of exercise and health related variables. Most CV estimates were similar or only slightly higher in athletes compared to those reported for the general population, whereas two- to three-fold increases were observed for amylase, ALT, AST and ALP. No effect of exercise and health related variables were observed on the CV estimates. For seven measurands, data were not homogeneously distributed and BV estimates were therefore not reported. The observation of higher CV estimates in athletes than what has been reported for the general population may be related to physiological stress over time caused by the continuous practice of exercise. The BV estimates derived from this study could be applied to athlete populations from disciplines in which they exercise under similar conditions of intensity and duration.